Integrating IT & OT : building a model based foundation (2017)
"The purpose of this thesis is to provide a foundation in order to integrate OT and IT. The thesis presents the modeling means (metamodel and language) that allow the description of business, IT, and OT structures, as well as the way in which they inter-twine. It is also necessary to have extension and configuration mechanisms that make it possible to address the concerns of specific industries and companies by adjusting the models and notations. Additionally, the thesis introduces a technique for constructing an indicator catalog based on a metamodel for OT with critical OT elements that generate information."--Tomado de la introducción.